Nanoscale Elastoplastic Wrinkling of Ultrathin Molecular Films - Gianfranco Cordella (MDPI AG, 2021)
Ultrathin molecular films deposited on a substrate are ubiquitously used in electronics, photonics, and additive manufacturing methods. The nanoscale surface instability of these systems under uniaxial compression is investigated here by molecular dynamics simulations. We focus on deviations from the homogeneous macroscopic behavior due to the discrete, disordered nature of the deformed system, which might have critical importance for applications. The instability, which develops in the elastoplastic regime above a finite critical strain, leads to the growth of unidimensional wrinkling up to strains as large as <semantics>0.5</semantics>. We highlight both the dominant wavelength and the amplitude of the wavy structure. The wavelength is found to scale geometrically with the film length, <semantics>λ∝L</semantics>, up to a compressive strain of <semantics>ε≃0.4</semantics> at least, depending on the film length. The onset and growth of the wrinkling under small compression are quite well described by an extended version of the familiar square-root law in the strain <semantics>ε</semantics> observed in macroscopic systems. Under large compression (<semantics>ε≳0.25</semantics>), we find that the wrinkling amplitude increases while leaving the cross section nearly constant, offering a novel interpretation of the instability with a large amplitude. The contour length of the film topography is not constant under compression, which is in disagreement with the simple accordion model. These findings might be highly relevant for the design of novel and effective wrinkling and buckling patterns and architectures in flexible platforms for electronics and photonics.